Three new and five known species of Diplopeltoides Gerlach, 1962 (Nematoda, Diplopeltoididae) from Sweden, and a revision of the genus - Holovachov, Oleksandr; Boström, Sven (European Journal of Taxonomy, 2017)
Eight species of Diplopeltoides are described from the Swedish west coast. Diplopeltoides suecicus sp. nov. has the cuticle with longitudinal striation visible only under SEM; cuticular plate underlying the cephalic cuticle around the amphid present; cephalic sensilla 4–6 µm long; amphid an inverted U-shape; wide space between amphidial branches areolated; spicules 27–31 µm long; gubernaculum with caudal apophysis. Diplopeltoides longicaudatus sp. nov. is characterized by a cuticle without longitudinal striation; cuticular plate underlying cephalic cuticle around amphid present; cephalic sensilla 13 µm long; amphid an inverted U-shape; narrow space between amphidial branches not ornamented; spicules unequal in size, 27–31 µm long; gubernaculum absent; midventral precloacal cuticular ridge present. D. grandis sp. nov. is characterized by a cuticle with longitudinal striation; cuticular plate underlying cephalic cuticle around amphid present; cephalic sensilla 18.5 µm long; amphid an inverted U-shape; wide space between amphidial branches punctate. The following taxonomic changes are proposed: Diplopeltoides asetosus (Juario, 1974) comb. nov., Diplopeltoides botulus (Wieser, 1959) comb. nov., Diplopeltoides bulbosus (Vitiello, 1972) comb. nov., Diplopeltoides lucanicus (Boucher & Helléouët, 1977) comb. nov., Diplopeltoides pumilus (Vincx & Gourbault, 1992) comb. nov. and Diplopeltoides striatus (Gerlach, 1956) comb. nov. Diplopeltoides holovachovi Fadeeva & Mordukhovich, 2013 is synonymised with Diplopeltoides pumilus comb. nov. An updated key to the species of Diplopeltoides is provided.